The effects of age, parity and body mass index on 50 g oral glucose tolerance test results and its predictive value in gestational diabetes mellitus - Deniz, Alparslan (Journal of Surgery and Medicine, 2020)
Aim: The aim of this study was to investigate the effects of age, parity, body mass index (BMI) and maternal risk factors on 50 g oral glucose tolerance test (OGTT) positivity and to evaluate the predictive value of 50 g OGTT in the diagnosis of gestational diabetes mellitus (GDM). Methods: Medical data of pregnant women who were followed in a private obstetrics and gynecology clinic between June 2012 and April 2020 were analyzed in this retrospective cohort study. All patients underwent 50 g OGTT between 24 and 28 weeks of gestation. A 1-h postprandial venous plasma glucose cut-off of ≥140 mg/dL was considered positive for OGTT and the diagnosis was confirmed by 2-h 75 g OGTT. The relationship between the GDM and OGTT results, BMI, parity, age, and other maternal risk factors was analyzed in the regression analysis. Results: A total of 323 pregnant women were included in the study. The mean age was 29.35 (5.29) years and the mean BMI was 27.23 (6.07) kg/m2. Among them, 35.9% had ≥1 risk factors. The sensitivity, specificity, positive predictive value, and negative predictive value of 50 g OGTT for GDM were 100%, 80.7%, 27.5%, and 100%, respectively. Regression analysis revealed that family history of diabetes, history of GDM, and macrosomic birth increased the GDM risk by 5.73, 4.95, and 1.43 folds, respectively. Conclusion: Evaluation of advanced maternal age, pre-pregnancy BMI, and maternal risk factors is useful to predict GDM. In addition, 50 g OGTT is helpful in diagnosing GDM for both maternal and fetal health.